First Year Student Perception in Hybrid Learning at University After Drastic Decline Covid-19 Cases - Baihaqi, Muhammad Wildan; Muflih, Ariq Barruttamam; Wahyunengsih, Wahyunengsih (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2022)
This study determines the perceptions of first-year students towards hybrid learning during the drastic decline of Covid-19 cases. This research uses a qualitative approach with descriptive methods conducted by first-year students from the Journalism Study Program at Syarif Hidayatullah State Islamic University (UIN) Jakarta. The results revealed that there were 4 subscales with positive perceptions including preparation for the Covid-19 pandemic (99%), academic adjustment (92%), social change (62%), institutional attachment (86%), and 1 subscale with negative perceptions, namely personal-emotional adjustment (73%). The conclusion from the results of the study is that of the five subscales, respondents’ perceptions refer to positive values. Although there is one subscale that has a high negative perception. Respondents can prepare and adjust themselves to learn with hybrid learning method. However, respondents need self-awareness regarding their mental and physical health.